2019
DOI: 10.1186/s12935-019-0885-z
|View full text |Cite
|
Sign up to set email alerts
|

Relation of AURKB over-expression to low survival rate in BCRA and reversine-modulated aurora B kinase in breast cancer cell lines

Abstract: Background New therapeutic drug for breast cancer (BRCA), especially triple negative BRCA (TNBC), is urgently needed. Even though 2-(4-morpholinoanilino)-6-cyclohexylaminopurine (reversine) is an aurora kinase inhibitor, it also inhibits some cancer cells and human BRCA cells. However, the potential roles of reversine as a novel therapeutic agent for the treatment of BRCA remains unknown and must be further investigation. Thus, the relationship of reversine to aurora kinase in BCRA has not been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 41 publications
5
30
1
1
Order By: Relevance
“…Likewise, AURKB was found to be induced in the squamous carcinoma subtype of NSCLC and the expression level of AURKB also served as a marker for resistance to paclitaxel, a drug commonly used in the treatment of NSCLC [ 31 ]. Similar to NSCLC, metastatic colorectal cancer patients lived significantly shorter when they had high levels of AURKB expression in their tumor tissues [ 32 ] and the publicly available databases further showed that increased AURKB expression also correlated significantly with reduced survival in breast cancer patients [ 33 ]. AURKB expression has been identified as a prognostic biomarker in glioblastoma [ 34 ], gastric cancer [ 35 ] and oral cancer [ 36 , 37 , 38 ].…”
Section: Deregulation Of Aurkb In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, AURKB was found to be induced in the squamous carcinoma subtype of NSCLC and the expression level of AURKB also served as a marker for resistance to paclitaxel, a drug commonly used in the treatment of NSCLC [ 31 ]. Similar to NSCLC, metastatic colorectal cancer patients lived significantly shorter when they had high levels of AURKB expression in their tumor tissues [ 32 ] and the publicly available databases further showed that increased AURKB expression also correlated significantly with reduced survival in breast cancer patients [ 33 ]. AURKB expression has been identified as a prognostic biomarker in glioblastoma [ 34 ], gastric cancer [ 35 ] and oral cancer [ 36 , 37 , 38 ].…”
Section: Deregulation Of Aurkb In Cancermentioning
confidence: 99%
“…Additionally, PHA680632 [ 139 ], reversine [ 33 , 140 ], CCT129202 [ 141 ], CCT137690 [ 142 , 143 ], SNS-314 [ 144 ], quercetin [ 145 , 146 ] are pan-aurora kinase inhibitors that have been tested in pre-clinical studies. Furthermore, VX-680 [ 147 , 148 , 149 ] and BI 811283 [ 108 , 109 ] are pan-AURK inhibitors that have been studied in clinical trials.…”
Section: Targeting Aurkb In Cancermentioning
confidence: 99%
“…Aurora kinase family comprises serine/threonine kinases that play critical roles in cell-cycle progression, chromosome alignment and cytokinesis during mitosis, and consists of three members: Aurora A, B and C. Aberrant expression of aurora kinases has been reported in human solid and hematological cancers 10 12 . Aurora B, the catalytic subunit of chromosomal passenger complex (CPC), is involved in multiple mitotic functions, and therefore dysfunction of its kinase activity will cause segregation barrier of chromosomes, central spindle assembly impairment, and phosphorylation of histone H3 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…AURKB plays a key role during mitosis [19].The role of the AURKB expression in cancer prognosis is controversial. AURKB was found to be correlated with the cell proliferation and AURKB expression is an independent prognostic index of breast cancer, especially for triple negative breast cancer (TNBC) [20,21]. While AURKB expression was reported to be not associated with the survival of breast cancer patients [22].…”
Section: Discussionmentioning
confidence: 99%